Developing the Fraction Triangle Card as an Instructional Media for Supporting Fifth Graders in Learning Multiplication of Fractions - Ummu Kaltsum Fathonah; Linda Astriani (Universitas Pendidikan Indonesia (UPI), 2023)
This development research is motivated by the unavailability of mathematics learning media that support the learning process, especially on fraction multiplication material. The purpose of this development research is to determine the validity and practicality of Fraction Triangle Card learning media. For this reason, research was conducted using the Research and Development (RD) method using the Analysis, Design, Development, Implementation, Evaluation (ADDIE) development model to test the validity and practicality of the Fraction Triangle Card learning media. This development research was conducted at SDN Cilandak Barat 04 Pagi in the academic year 2023/2024 odd semester. For the validation test, this learning media was conducted by three experts, namely language experts, media experts, and material experts while to test practicality it was carried out in stages, namely teacher practical trials, small group trials, and large group trials. The results showed that the Fraction Triangle Card learning media was very valid based on the results of the calculation of linguists with a percentage assessment of 84%, media experts with a percentage assessment of 90%, and material experts with a percentage of 88%. The results of the teacher's practicality trial obtained a percentage assessment of 93.3%, the results of the small group trial obtained a percentage assessment of 98.61%, and the results of the large group trial obtained a percentage assessment of 94.4%. Based on the results of the study, the Fraction Triangle Card learning media is very valid and practical to be used by fifth grade elementary school students.